2023
DOI: 10.1111/jcmm.17677
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐biotechnology in tumour and cancerous disease: A perspective review

Abstract: In recent years, drug manufacturers and researchers have begun to consider the nanobiotechnology approach to improve the drug delivery system for tumour and cancer diseases. In this article, we review current strategies to improve tumour and cancer drug delivery, which mainly focuses on sustaining biocompatibility, biodistribution, and active targeting. The conventional therapy using cornerstone drugs such as fludarabine, cisplatin etoposide, and paclitaxel has its own challenges especially not being able to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 258 publications
1
11
0
Order By: Relevance
“… 29,30 Reports also have shown that smaller nanoparticles can extravasate more easily through leaky tumor vasculature and penetrate deeper into tissues, increasing their chances of encountering cancer cells. 31,32 We speculate that the novel NA with a size range of less than 100 nm will have a higher cellular uptake rate, enhanced permeability, and retention effect as previously reported by various nanosystems. Since NA are stable at acidic pH, they can resist the acidic environment of endosomes preventing premature drug release and ensure that the cargo reaches the cytoplasm where the drug can exert its therapeutic effect with less concentration, thus reducing drastic side effects.…”
Section: Resultssupporting
confidence: 60%
“… 29,30 Reports also have shown that smaller nanoparticles can extravasate more easily through leaky tumor vasculature and penetrate deeper into tissues, increasing their chances of encountering cancer cells. 31,32 We speculate that the novel NA with a size range of less than 100 nm will have a higher cellular uptake rate, enhanced permeability, and retention effect as previously reported by various nanosystems. Since NA are stable at acidic pH, they can resist the acidic environment of endosomes preventing premature drug release and ensure that the cargo reaches the cytoplasm where the drug can exert its therapeutic effect with less concentration, thus reducing drastic side effects.…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, there are only a few compounds for pulmonary administration on the existing list of pharmaceutical additives [260]. Many other researchers have also reviewed the nano-TB options for treatment, providing a deep overview of the knowledge and technologies available [261][262][263][264][265].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Nanoscale materials and structures can be engineered to interact with biological systems at the molecular level, enabling targeted drug delivery, sensitive diagnostic methods, and precise imaging techniques. Nanobiotechnology has the potential to revolutionize healthcare, environmental monitoring, and energy production (Maurya, Mukherjee, & Ranjan, 2023;Soni et al, 2023).…”
Section: Nanobiotechnologymentioning
confidence: 99%